Analisis Tindak Tutur Asertif dalam Film “Sweet 20” Karya Ody C. Harap - Nilam Aliya Putri; Sagita Tiara Dewi; Fiky Nafian; Izmi Ayyita Rahmawati; Syavrina Fatwa Aulia; Asep Purwo Yudi Utomo; Ahmad Ripai; Rosita Rahma (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study is based on the urgency of understanding assertive speech acts as part of pragmatic studies in speech acts in the movie Sweet 20 by Ody C. Harap. Sweet 20 was chosen because of its richness in dialogue and cross-generational representation, thus allowing in-depth analysis of speech acts. This research aims to identify, classify, and analyze the form and function of assertive speech acts used by the characters in the film. The method used in this research is descriptive qualitative with a pragmatic approach. The data were obtained through listening and note-taking techniques on the characters' speech in the movie. Data analysis refers to Searle and Galassi's speech act theory, which emphasizes assertive speech acts. The results show various forms of assertive speech acts, such as stating, telling, suggesting, boasting, complaining, reporting, expressing positive emotions, self-affirmation, and expressing negative emotions, which are influenced by the social and cultural context in the movie. This research contributes to the development of pragmatics studies in linguistics, can be used as a reference in learning Indonesian, especially speaking skills, and provides further insight into the use of speech acts in audio-visual media.